2011
DOI: 10.1002/jnr.22584
|View full text |Cite
|
Sign up to set email alerts
|

Different spatial and temporal protein expressions of repulsive guidance molecule a and neogenin in the rat optic nerve after optic nerve crush with and without lens injury

Abstract: The failure of lesioned mammalian CNS neurons to regenerate their axons remains a challenge. Evidence is emerging that repulsive proteins contribute to this failure. The repulsive guidance molecule A (RGMA) induces growth cone collapse in vitro, accumulates in the scar after spinal cord injury, and is up-regulated in glaucoma. In this study, we evaluated the spatial and temporal localization pattern of RGMA and its receptor neogenin in the optic nerve after optic nerve crush (ONC) without or with lens injury (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 69 publications
2
13
2
Order By: Relevance
“…We localized RGMA at the crush site immediately after ONC alone, and RGMA remained present from there on, whereas it was always absent in the ONC + LI animals [25]. In all investigated groups (including control and sham animals), many cells were found to be RGMA+ in the ON: nerve fibers, blood vessel endothelial cells, astrocytes, oligodendrocytes, some microglial cells, and the shaft of the optic nerve.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…We localized RGMA at the crush site immediately after ONC alone, and RGMA remained present from there on, whereas it was always absent in the ONC + LI animals [25]. In all investigated groups (including control and sham animals), many cells were found to be RGMA+ in the ON: nerve fibers, blood vessel endothelial cells, astrocytes, oligodendrocytes, some microglial cells, and the shaft of the optic nerve.…”
Section: Discussionmentioning
confidence: 96%
“…We recently showed that RGMA was present at the crush site after optic nerve crush (ONC) and absent after ONC + lens injury (LI). RGMA was co-localized with nerve fibers, blood vessels, shaft of the ON, astrocytes, oligodendrocytes, and some microglial cells [25]. Moreover, we showed a significantly lowered amount of RGMA in ONC plus LI animals at 2, 4, and 6 days after crush compared to ONC animals [25].…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations